Digital ecosystems and their implications for competitive strategy - Mohan Subramaniam (Journal of Organization Design, 2020)
This paper discusses some implications for competitive strategy when business environments are framed as digital ecosystems. Digital ecosystems are ecosystems shaped by interdependencies initiated through data connectivity, galvanized by technologies such as sensors and the Internet of Things (IoT). They are composed of two parts: production and consumption ecosystems. Production ecosystems are founded upon interdependencies associated with value chains. Although their underlying interdependencies are traditional, they gain fresh impetus because of data connectivity. Consumption ecosystems on the other hand are spawned by interdependencies among entities that complement the data generated by product usage. These are largely new interdependencies that did not exist before modern digital technologies enabled connectivity. Taken together, digital ecosystems influence a firm's strategic landscape. I discuss three implications of digital ecosystems for competitive strategy: (1) the scope of value creation, (2) the scope of competition, and (3) the rise of digital monopoly power. I also discuss the implications of digital ecosystems for organizational design and suggest how studies can assess the processes driving the digitization of ecosystems.
Keywords: 650; Digital ecosystems; Competitive strategy; Platforms